2017
DOI: 10.3389/fnbot.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Step-to-Step Ankle Inversion/Eversion Torque Modulation Can Reduce Effort Associated with Balance

Abstract: Below-knee amputation is associated with higher energy expenditure during walking, partially due to difficulty maintaining balance. We previously found that once-per-step push-off work control can reduce balance-related effort, both in simulation and in experiments with human participants. Simulations also suggested that changing ankle inversion/eversion torque on each step, in response to changes in body state, could assist with balance. In this study, we investigated the effects of ankle inversion/eversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
(81 reference statements)
1
34
0
Order By: Relevance
“…Later studies showed that CoP shifts are also used after perturbations [ 13 , 19 ]. In a recent study, Kim & Collins [ 115 ] showed that in amputees, the effort associated with balance (e.g. energetic cost) could be reduced by appropriate control (inversion/eversion torque) of a robotic prosthesis, further highlighting the importance of stance leg control.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies showed that CoP shifts are also used after perturbations [ 13 , 19 ]. In a recent study, Kim & Collins [ 115 ] showed that in amputees, the effort associated with balance (e.g. energetic cost) could be reduced by appropriate control (inversion/eversion torque) of a robotic prosthesis, further highlighting the importance of stance leg control.…”
Section: Discussionmentioning
confidence: 99%
“…However, we tested five different control architectures, four vastly different from each other. Both the neuromuscular and the balance controller have been successfully used in the past to reduce the metabolic cost of walking with an active prostheses below that of walking with a passive prosthesis 18,20 . In addition, the time-based torque controller is similar to one that has been successfully used to reduce the metabolic cost of walking with exoskeletons 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The second approach focuses on balance assistance in the form of ankle inversion or eversion torque in response to changes in center of mass velocity. Implementing such control in an ankle-foot prosthesis emulator led to reductions in energy expenditure during walking by 9%, when compared to walking with passive prostheses 20 . Although these results are promising, simulations demonstrate that active prostheses have more potential to mitigate problems faced by individuals with amputation, with the possibility of reducing the metabolic cost of walking to more than 70% less than unimpaired walking 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of active prosthesis focused mainly on the aspects of improving propulsion on the impaired limb but did not explicitly consider dynamic balancing aspects, particularly not in the context of coping with unexpected perturbations (Windrich et al, 2016). Few studies investigated effects of stiffness properties of the prosthetic leg on balance in the sagittal (Major et al, 2016) and frontal plane (Kim and Collins, 2017). They showed that appropriate control of stiffness in the arti cial ankle joint may improve balance in terms of reduced variability and asymmetry in spatio-temporal parameters during unperturbed walking at self-selected speed.…”
Section: Clinical Relevancementioning
confidence: 99%